Determination of the critical contact separation length for DC interruption in a vacuum subject to an external transverse magnetic field - Ma, Hui; Liu, Shaowei; Chen, Jinlong; Yu, Chen; Geng, Yingsan; Liu, Zhiyuan; Wang, Jianhua (Physics of plasmas, 2023)
The objective of this work is to experimentally determine the critical contact separation length Lcritical for DC interruption in vacuum under an external transverse magnetic field (TMF), according the interruption behaviors and vacuum arc characteristics. L is defined as the separation length at the instant of TMF application. Lcritical is the critical and the minimal necessary separation length of the contacts for a successful DC interruption in vacuum. A pair of Helmholtz coils was used to generate the external TMF. A high-speed camera was used to record the vacuum arc appearance. The experimental results quantitatively determine Lcritical for DC vacuum interruption under a certain DC and the external TMF. When the DC ranged from 100 to 500 A under an external TMF of 30 mT, Lcritical ranged from 2.1 to 3.7 mm and did not show linear variation. Second, the extinguishing time of DC vacuum interruption te at various currents significantly increased in a similar pattern under decreasing L in the range of 0.3–1.6 ms. The decrease in L mainly increased the duration of the stable stage and had little apparent influence on the duration of the unstable stage of the DC vacuum arc. Third, the physical mechanism determining Lcritical in DC vacuum interruption under a TMF could be explained from two aspects: the expansion of the vacuum arc column and the diffusion of the metal plasma. In successful DC vacuum interruption, Lcritical should be large enough for the formation and expansion of the “C”-shaped arc column, and enough space should be available for the diffusion of the metal plasma.